Optimizing User Experience - A Design-Driven Approach to Enhancing Web Application Interfaces - Pham, Kevin (My University, 2024)
This Master’s thesis delves into the realm of user-centered design principles and their impact on optimizing user experience through a design-driven approach in web application interfaces. Focused on the relatively unexplored domain of configuration systems, the study aims to deepen our understanding of how user expertise influences user experience, bridging the gap between designers and programmers. By combining interaction design principles with data engineering knowledge, the research seeks to enhance the existing body of knowledge in UX design for configuration systems. The thesis outlines the design process of the user interface for an existing application, emphasizing frontend programming aspects and interaction design methodologies. A Minimum Viable Product (MVP) prototype is developed to improve usability, performance, feedback, functionality, and visual design in web interfaces. Evaluation results confirm the positive trajectory of the prototype design, showcasing enhancements in user experience aspects. Reflecting on the challenges faced and insights gained, the thesis offers recommendations for future research, highlighting potential avenues for exploration and the ongoing evolution of design practices. The study advocates for challenging established design principles to foster innovation and creativity in interface design, paving the way for transformative advancements in user interface design and user experience optimization. Overall, this thesis serves as a foundational step in the exploration of user-centered design principles in configuration systems, providing valuable insights for researchers and practitioners in the field of Interaction Design & Technologies.
Keywords: Human-computer interaction; Rapid prototyping; User Experience; Design Process; Constructive Design Research; User-Centered Design; User Interface